The Dry Cleaner's Best Friend! - Dow Chemical Company (1937)
Color print advertisement for Dow Chemical Company depicts a man and woman sitting at a soda fountain counter with a waiter interacting with them. The woman spills ice cream on her dress with a dog by her side lapping up what has spilled on the floor. The accompanying paragraph discusses Dow technicians' work to produce safer, organic and superior dry cleaning solvents than used previously.
Keywords: Soda fountains; Chemical industry; Dow Chemical Company; Corporations; Advertising; Dry cleaning industry